Qualitative and quantitative evaluation of Oroxylum indicum (L.) Kurz by HPLC and LC‐qTOF‐MS/MS. (4th September 2019) - Peng, Qian; Shang, Xueying; Zhu, Chenchen; Qin, Shengying; Zhou, Yuan; Liao, Qiongfeng; Zhang, Ren; Zhao, Zhongxiang; Zhang, Lei
Abstract: Oroxylum indicum, as a popular functional Chinese herbal medicine for reducing hyperactivity, relieving sore throat, smoothing the liver and adjusting stomach, mainly contains flavonoids. In this study, we aimed to establish a fast and sensitive method that enables to analyze the chemical components in O. indicum qualitatively and quantitatively. First, a total of 42 components were characterized by LC‐quadrupole time‐of‐flight (qTOF)‐tandem mass spectrometry (MS/MS), including 23 flavonoid glycosides, 13 flavonoids and six other types of compounds. Then, 17 characteristic components of the 19 common peaks in the chromatographic fingerprints of O. indicum were confirmed. Fifty samples were classified into two groups by hierarchical clustering analysis and orthogonal partial least squares‐discriminant analysis, which also identified the 10 main chemical markers responsible for differences between samples. Last, the quantitative analysis of multiple components with a single marker method was established for simultaneous determination of six main active components in O. indicum by LC‐UV with oroxin B was chosen as internal reference substance. Finally, a rapid and efficient method integrating HPLC with LC‐electrospray ionization‐qTOF‐MS/MS analysis was established to comprehensively discriminate and assess the quality of O. indicum samples.